Jawaban:
f(x)^-1 = (2 - x)/(2x - 1) ,x ≠ ½
Penjelasan dengan langkah-langkah:
f(x) = (x + 2)/(2x + 1)
y = (x + 2)/(2x + 1)
y(2x + 1) = x + 2
2xy + y = x + 2
2xy - x = 2 - y
x(2y - 1) = 2 - y
x = (2 - y)/(2y - 1)
f(y)^-1 = (2 - y)/(2y - 1)
f(x)^-1 = (2 - x)/(2x - 1)
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Jawaban:
f(x)^-1 = (2 - x)/(2x - 1) ,x ≠ ½
Penjelasan dengan langkah-langkah:
f(x) = (x + 2)/(2x + 1)
y = (x + 2)/(2x + 1)
y(2x + 1) = x + 2
2xy + y = x + 2
2xy - x = 2 - y
x(2y - 1) = 2 - y
x = (2 - y)/(2y - 1)
f(y)^-1 = (2 - y)/(2y - 1)
f(x)^-1 = (2 - x)/(2x - 1)